The Syrian stratum of the Ukrainian toponymics (the Byzantine time) - ТИЩЕНКО, К. (Київський національний університет імені Тараса Шевченка, 2020)
The article highlights the important consequences of reliable identification of the group of place names Zhabye as replicas of the prototype Jābiya – the capital of the Ghassanid (Byzantine federates in the VI–VII century). Thanks to this, it became possible to systematize already studied Ukrainian replicas of the Byzantine age names-prototypes from Syria. Among the selected prototypes in the Middle East are: toponyms 'Asqalan, Callinicum / Raqqa, Dimashq Damascus, Fihl, Halab, ḤAWRĀN, Jābiya, Jarash, JIBAL, Quds = Bayt al-Maqdis Jerusalem, Laodicaea/ Ladhiq, Palmyra, PHOENICIA, Ruṣāfa/ Sergiopolis / Ῥάφες, Tiberias, Tripolis, Bilad al-SHAM / SURIYEH Syria, Yathrib/ Medina; anthroponyms Theodosius, Ya'qūbī Jacob Baradaeus. As of 2019, highly reliable replicas of these prototypes were discovered in Ukraine: Oskolonivka, Skalonivka, Kalynuvatka, Kalynivka (over 80 place names), Raky, Rachyntsi, Damasky, Demeshkivtsi, Fyholivka, Khalepya, Khaleptsi, Tverdokhliby (3), Havrontsi, Havronshchyna, Zhabelivka, group Zhabye (20), Yaroshi (4), Yaroshivka (4), Yaryshiv, Chepelivka, group Kutsivka, Mahdyn, Ladyzhyn (6), Pal'myrivka, Ponykva, Ponykovytsia, Rusava, Rosava (4), Rasavka, Rosokha, Rosokhovatka, Serhiyi, Tyvriv (2), Trypill'a (2), Shamy / Surzha, Surozh, Yastrub- (14), Pedosy, Khodosy, Yakubivka e. a. The first replicas of this vector (Tripol, Khalep, Korsun') were pointed out by V. Z. Zavytnevytch and A. I. Sobolevsky as similar to the Byzantine place names. The remaining synchoric names were identified with varying degrees of reliability by the method of toponymic contextualization in 2008–2019. Moreover, if each individual replica can be challenged, their mutual conditionality acquires a new scientific quality (V. I. Abaev). The current find of the initial territory with a concentration of synchoric and synchronous prototypes of this vector of toponyms-replicas in Ukraine radically improves scientific ideas about the whole picture of contacts between the steppe and forest-steppe population of the Dnieper region with Byzantium in the pre-chronicle time (IV–IX centuries).

Висвітлено етапні наслідки ідентифікації групи топонімів Жаб'є як реплік прототипу Jābiya: то була назва столиці гасанідів, християнізованих арабів-федератів Візантії VI–VII ст. Ця ідентифікація уможливила системне зведення всієї множини раніше вивчених історичних реплік в Україні назв-прототипів із Сирії візантійського часу. Серед врахованих прототипів на Близькому Сході: топоніми – 'Asqalan Аскалан, Callinicum Калінік / Raqqa Ракка, Dimashq Дамаск, Fihl Фіхль, Halab Халеб, ḤAWRĀN гори аль-Хауран, Jābiya Джабія, Jarash Джараш, JIBAL Джибал, Quds = Bayt al-Maqdis Єрусалим, Laodicaea / Ladhiq Лаодікея, Palmyra Пальмира, PHOENICIA Фінікія, Ruṣāfa / Sergiopolis / Ῥάφες Русафа, Tiberias Тиверіада, Tripolis Триполіс, Bilad al-SHAM Шам / SURIYEH Сирія, Yathrib / Medina Ясріб; антропоніми –Theodosius Феодосій, Ya'qūbī Jacob Baradaeus. Вірогідні репліки цих прототипів в Україні станом на 2019 р.: Осколонівка, Скалонівка, Калинуватка, Калинівка (понад 80 назв), Раки, Рачинці, Дамаски, Демешківці, Фиголівка, Халеп'я, Халепці, Твердохліби (3), Гавронці, Гавронщина, Жабелівка, група Жеб'є (20), Яроші (4), Ярошівка (4), Яришів, Чепелівка, група Куцівка, Магдин, Ладижин (6), Пальмирівка, Пониква, Пониковиця, Русава, Росава (4), Расавка, Росоха, Росоховатка, Сергії, Тиврів (2), Трипілля (2), Шами / Суржа, Сурож, Яструб- (14), Педоси, Ходоси, Якубівка та ін. Перші візантійські прототипи реплік цього вектора (Триполь, Халѣпъ, Корсунь) припустили ще В. З. Завитневич і О. І. Соболевський (1888, 1911). Решту синхоричних назв із різним рівнем вірогідності віднайдено методом топонімічного контекстування у 2005–2019 рр. Поетапно розкриваються фрагменти автентичної давньої системи назв, що згодом зазнали ряду закономірних і випадкових звукових змін і переосмислень. Теперішня знахідка цілої вихідної території у Сирії та Палестині з великою концентрацією прототипів цього вектора топонімів-реплік України надає нової якості науковим уявленням про зміст і форми контактів із Візантією степових і лісостепових племен Наддніпрянщини в долітописний період (IV–IX ст.).
Сирійський пласт топонімії України візантійського часу
Keywords: Візантія; Сирія; Палестина; араби-християни; топонімія України; мовні контакти; Сирійський пласт топонімії України; Byzantium; Syria; Palestine; Arabs-Christians; toponymy of Ukraine; language contacts; The Syrian stratum of the Ukrainian toponymics